The phytochemistry and chemotherapeutic potential of Tasmannia lanceolata (Tasmanian pepper): A review - IE, Cock (Pharmacognosy Communications)
Plants contain a myriad of natural compounds which exhibit important bioactive properties. These compounds may provide alternatives to current medications and afford a significant avenue for new drug discovery. Despite this, little information is available in the literature regarding many native Australian plants and their potential for medicinal and industrial uses. Tasmannia lanceolata (Tasmanian pepper) has a long history of usage by Australian Aborigines and European settlers as a food flavouring agent. Aborigines also used it for the treatment and cure of skin disorders, venereal diseases, colic, stomach ache and as a quinine substitute. Apart from the reported ethnopharmacological uses of Tasmanian pepper, surprisingly few studies have rigorously examined this species for its medical properties. Recent studies have reported Tasmanian pepper to be an extremely good source of antioxidants. Indeed, Tasmanian pepper has been reported to have free radical scavenging activities more than 4 times higher thanblueberries despite having ascorbic acid levels below the level of detection. Tasmanian pepper is particularly high in terpenes and phenolic compounds but also has high levels of a variety of other antioxidants, including anthrocyanins and anthrocyanins glycosides. Antioxidants have been associated with the prevention of cancer, cardiovascular disease and neurological degenerative disorders. They are also linked with anti-diabetic bioactivities and have been associated with the reduction of obesity. Antioxidants can directly scavenge free radicals, protecting cells against oxidative stress related damage to proteins, lipids and nucleic acids. Therefore, T. lanceolata has potential in the treatment of a variety of diseases and disorders and its potential bioactivities warrant further investigation.
Keywords: Winteraceae; Tasmannia lanceolata; Tasmanian pepper; Australian medicinal plants; antioxidants; flavonoids; terpenoids